Description of the immatures of workers of the weaver ant, Camponotus textor (Hymenoptera: Formicidae) - Solis, Daniel Russ [UNESP]; Fox, Eduardo Gonçalves Paterson [UNESP]; Rossi, Mônica Lanzoni; Bueno, Odair Correa [UNESP] (My University, 2009)
The weaver ants Camponotus textor (Forel) (Hymenoptera: Formicidae) are native to Central and South America, where they use their larvae to build silken nests by sewing tree leaves together. Few studies have been conducted with this species, and little is known about the morphology of their larvae. The present paper estimated the number of larval instars of C. textor and presents a detailed morphological description of each immature stage based on light and electron microscopic observations. The number of larval instars was estimated as four based on the frequency distribution of larval head widths. The larvae of this species presented some typical characteristics of Camponotus (Mayr) larvae: body shape 'pogonomyrmecoid', ten pairs of spiracles, antennae with three sensilla, conspicuous 'chiloscleres' on the labrum, and mature larvae with pronounced labial pseudopalps. Unprecedented characteristics would include: great diversity of body hair types, and 'camponotoid' mandibles but with four medial denticles. This information can aid biological and taxonomic studies with these ants, and may be useful for ant systematics.
Keywords: Camponotini; Formicinae; Larval instars; Myrmobrachys; Post-embryonic development